IDEAL AGE AT FIRST MARRIAGE IS STILL BELOW THE LEGAL AGE OF MARRIAGE- THE CASE OF ADOLESCENT GIRLS IN WEST HARARGE ZONE, EASTERN ETHIOPIA - Edossa, Wasihun; Berhane, Yemane; Worku, Alemayehu; Tesfa, Anene; Worku, Amare; Gulema, Hanna; Fassil, Nebiyou; Tewahido, Dagmawit; Tesfaye, Selamawit (Ethiopian Journal of Reproductive Health, 2021)
BACKGROUND Early marriage is a harmful practice associated with serious adverse health and social outcome. It is common practice in a male-dominated society. Ethiopia has legislative provisions and stakeholders advocating for the abolition of early marriage, however, the practice appears to continue due to perceived ideal age, which has not been monitored regularly. The aim of this study was to determine the ideal age at first marriage among adolescent girls and assess the role of influencers for early marriage in West Hararge Zone, Eastern Ethiopia. METHODS Descriptive analysis of the ideal age for first marriage was done as part of a large cross-sectional survey. Participants were female adolescent girls 13-17 years of age, male reference groups, and female reference groups. Both quantitative and qualitative data were used. Data were cleaned with (SPSS version 20) and analyzed by STATA/SE version 13 and summarized by descriptive statistics. A thematic data analysis approach was utilized to summarize qualitative data. RESULTS The reported mean ideal age at first marriage by adolescent girls was 16.96 (95% CI: 16.81,17.11). The qualitative component of the study also revealed that girls still marry between the ages of 12 and 15 years. Family, peer pressure, marriage intermediaries, and community as a whole were found to influence decisions of young adolescent girls to marry early. CONCLUSION In conclusion, the Ideal age at first marriage of adolescent girls’ in selected districts of West Hararge is below the legal age of marriage in Ethiopia which is 18 years. This implies early marriage is still common practice in this study area. Since the role of family, peers, religious and community leaders were found significant, in addition to young adolescent girls, working with all influential group and community as a whole could be necessary to decrease and eliminate early marriage Keywords: Ideal age at first marriage, Legal age, early marriage